Providing official Statistics for the Common Market and Monetary Union in the Gulf Cooperation Council (GCC) Countries : A Case for "Gulfstat" - Al-Mansouri, Abdulrahman (IMF Working Papers; Working Paper, 2006)
The six member states of the Gulf Cooperation Council (GCC)-Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and United Arab Emirates (UAE)-have laid out a path to a common market by 2007 and monetary union by 2010, based on economic convergence. To monitor convergence and support economic and monetary policy, comparable economic data for member countries and data for the region as a whole will be essential. What is the most efficient way to produce these data? The authors survey the statistical institutions in the GCC countries and present the case for creating "Gulfstat"-a regional statistical agency to operate within a "Gulf States System of Statistics." Valuable lessons can be learned from regional statistical organization in Africa and the European Union-Afristat and Eurostat.